Soles, J, The House of the Metal Merchant and Other Buildings in the Neopalatial Town - Wallace , Saro (Journal of Greek Archaeology, 2024)
In 1908, Richard Seager commenced excavations on the prehistoric promontory of Mochlos (now an islet off Crete’s northeast coast) which was inhabited between at least the Early Bronze Age (Early Minoan I/II) and the Late Minoan IIIB period - i.e. c. 2900- 1200 BC, with Hellenistic and Roman re-settlement. This volume mainly addresses the results of further, systematic investigations, using more modern methodologies, of up to fifteen Middle Minoan IIIA-Late Minoan IB (c. 1750-1500 BC) domestic and ceremonial buildings partially excavated by Seager (some houses being multi-storey by their final use, with ashlar masonry construction, colour-plastered walls and floors; stone staircases; roof and street drains; kitchens with cooking holes/platforms and stone processing basins; storage and living rooms) located on the south coast of the present-day islet. Occupation was already present on the Cretan coast immediately south of the promontory by the LM IB period, and both areas had continued settlement and cemetery use into LM III.